Antimicrobial and enzymatic activity of actinomycetes isolated from soils of coastal islands - Ivana Charousová; Juraj Medo; Eva Halenárová; Soňa Javoreková (Wolters Kluwer Medknow Publications, 2017)
Microbiological investigation of unexplored ecosystems is crucial for discovering of antibiotic producing actinomycetes. The present study was conducted to determine antimicrobial activity and identify the most active strains. Actinomycetes were isolated using the spread plate technique following by serial dilution of samples on starch casein agar. The screening method consists of primary and secondary testing. The most active isolates were identified based on molecular and cultural methods. 42 out of 66 isolates displayed antimicrobial potential. 63% exhibited antibacterial activity, 16% antifungal activity, and 16% displayed both activities. Identified isolates, Streptomyces scabrisporus, Streptomyces sparsogenes, Streptomyces misakiensis, Streptomyces cirratus, Streptomyces lincolnensis, Streptomyces endophyticus, Streptomyces chartreusis, and Streptomyces alboniger showed a broad spectrum of enzymatic activities. The results indicated that these isolates may serve as antibiotic and enzyme-producing microbes.